2016
DOI: 10.1002/chem.201604179
|View full text |Cite
|
Sign up to set email alerts
|

[Ag(OH2)2][Ag(SO4)2]: A Hydrate of a Silver(II) Salt

Abstract: When exposed to air at ambient conditions, AgSO slowly reacts with moisture, yielding AgSO ⋅H O. The crystal structure determination (powder data) shows that it may be described as [Ag(OH ) ][Ag(SO ) ], with some sulfate groups being shared between different Ag cations, resembling in that way its Cu analogue. [Ag(OH ) ][Ag(SO ) ], the first hydrate of a compound of Ag , was extensively characterized using many physicochemical methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 42 publications
(105 reference statements)
0
13
0
Order By: Relevance
“…X‐ray powder diffraction, thermogravimetric calorimetric analysis, and Raman scattering spectra confirmed that pure Ag II SO 4 was obtained (see the Supporting Information) , . The crystals were much larger (up to 250 µm in length) and much less water sensitive than those obtained by using chemical synthesis; indeed, electrochemically prepared AgSO 4 reacts very slowly with atmospheric moisture to yield a monohydrate, rather than immediately decomposing into Ag I HSO 4 , as is the case for chemically prepared samples.…”
Section: Resultsmentioning
confidence: 56%
“…X‐ray powder diffraction, thermogravimetric calorimetric analysis, and Raman scattering spectra confirmed that pure Ag II SO 4 was obtained (see the Supporting Information) , . The crystals were much larger (up to 250 µm in length) and much less water sensitive than those obtained by using chemical synthesis; indeed, electrochemically prepared AgSO 4 reacts very slowly with atmospheric moisture to yield a monohydrate, rather than immediately decomposing into Ag I HSO 4 , as is the case for chemically prepared samples.…”
Section: Resultsmentioning
confidence: 56%
“…The on‐site interactions were included for each of the elements with the Hubbard term U set 5 eV for Ag ( l= 2), 2 eV for S ( l= 1) and 4 eV for O ( l= 1), and exchange term J set equally for all the atoms (1 eV). A similar computational setup can be found in other studies of silver(II) sulfate and sulfate hydrate [13,15,20] . For the spin non‐polarized DFT single‐point calculations the k‐spacing was set to 0.15 Å −1 .…”
Section: Methodsmentioning
confidence: 99%
“…A similar computational setup can be found in other studies of silver(II) sulfate and sulfate hydrate. [13,15,20] For the spin non-polarized DFT single-point calculations the k-spacing was set to 0.15 Å À 1 . For the more resourcedemanding spin-polarized calculations with HSE06 hybrid functional, the k-spacing was set to 0.30 Å À 1 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations